Implementasi DFT pada pemrograman berorientasi objek untuk menghitung struktur pita energi dengan The projector augmented wave (PAW) pada karbon, silikon dan germanium - Alfianto, Enggar
This study implemented DFT method into C++ language with object oriented rules (expressive software). The objective of using expressive software is to get a programming structure easy and has a similar structure with mathematical formula. In order of that can be improved easily by science community. The calculation of band energy structure is used the projector augmented wave (PAW) method. As validation, a silica with FCC structure has been chosen to calculate its band energy structure. The result of this calculation has been compared with Quantum Espresso software.